Regulation of Seed Germination and Abiotic Stresses by Gibberellins and Abscisic Acid - Vishal, Bhushan; Kumar, Prakash P. (Frontiers in Plant Science, 2018)
Overall growth and development of a plant is regulated by complex interactions among various hormones, which is critical at different developmental stages. Some of the key aspects of plant growth include seed development, germination and plant survival under unfavorable conditions. Two of the key phytohormones regulating the associated physiological processes are gibberellins (GA) and abscisic acid (ABA). GAs participate in numerous developmental processes, including, seed development and seed germination, seedling growth, root proliferation, determination of leaf size and shape, flower induction and development, pollination and fruit expansion. Despite the association with abiotic stresses, ABA is essential for normal plant growth and development. It plays a critical role in different abiotic stresses by regulating various downstream ABA-dependent stress responses. Plants maintain a balance between GA and ABA levels constantly throughout the developmental processes at different tissues and organs, including under unfavorable environmental or physiological conditions. Here, we will review the literature on how GA and ABA control different stages of plant development, with focus on seed germination and selected abiotic stresses. The possible crosstalk of ABA and GA in specific events of the above processes will also be discussed, with emphasis on downstream stress signaling components, kinases and transcription factors (TFs). The importance of several key ABA and GA signaling intermediates will be illustrated. The knowledge gained from such studies will also help to establish a solid foundation to develop future crop improvement strategies.